Mozart effect in patients with epilepsy - Ya. B. Skiba; M. M. Odinak; A. Yu. Polushin; M. Yu. Prokudin; M. V. Selikhova; S. N. Bardakov; M. Yu. Ratanov; V. I. Pustovoyt (Эпилепсия и пароксизмальные состояния, 2021)
Objective: to analyze available publications assessing efficacy of the Mozart effect in patients with epilepsy.Material and methods. A search for scientific publications has been performed in PubMed, Scopus and eLibrary databases by retrieving inquiries "Mozart effect" and "epilepsy" in paper title, resume and keywords. As a result, 18 studies matching inclusion and exclusion criteria were selected. The data obtained were systematized into four categories: 1) whether a single listening of Mozart’s Sonata for Two Pianos in D major, K.448 affect interictal epileptiform activity (IEA) immediately during an event; 2) whether a repeated (course) of listening K.448 affect IEA; 3) is there a delayed effect on IEA after a single or repeated listening of K.448; 4) how does the Mozart effect act on rate of epileptic seizures during ongoing therapy course of listening K.448 or afterwards.Results. It was found that therapy with Mozart’s sonata K.448 may lower IEA index during a single listening of this musical composition and shortly afterwards. A lowered IEA index during a course listening of K.448 lasting for some time afterwards may be observed as well. Moreover, a repeated listening of K.448 may reduce rate of epileptic seizures within entire music course.Conclusion. The analysis revealed that there are currently some reasons to consider the Mozart effect as a means of neurostimulation impacting on rate of epileptic seizures and IEA.